ANALISIS SIA PERSEDIAAN PADA PENYAJIAN LAPORAN KEUANGAN BPKA DIY TAHUN 2023 - Firmanda Azhar Nugraha; Agung Slamet Prasetyo (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
Indonesia's financial reforms, starting in 2003, introduced accrual-based Government Accounting Standards (PP No. 71/2010) for transparent and efficient financial management. The Provincial Government of Yogyakarta (DIY) is required to produce accurate financial reports, including inventory management under PSAP No. 05. BPKA DIY plays a key role but faces challenges due to discrepancies between financial and inventory systems. This study examines the importance of an integrated inventory accounting system in improving the quality of financial reporting at BPKA DIY, offering recommendations to enhance efficiency and transparency.